Pemberian Air Kelapa Muda Pada Tn. S dengan Diagnosis Hipertensi di Desa Awang Bangkal Barat Kecamatan Karang Intan: Studi Kasus - Khairi, Farid Akhmad Abdi; Agianto (School of Nursing, Faculty of Medicine and Health Science, Lambung Mangkurat University., 2023)
Background: People in the wetland area have an unfavorable lifestyle, which is fond of consuming vegetables with coconut milk such as gangan humbut with salty food (Ikan Wadi) and fried foods, from this habit the managed clients often feel headaches. Objective: To apply nursing care by giving young coconut water to patient S with a diagnosis of hypertension in Awang Bangkal Barat Village, Karang Intan distric.